Resilient plant monitoring systems: Techniques, analysis, design, and performance evaluation. (August 2015) - Garcia, Humberto E.; Meerkov, Semyon M.; Ravichandran, Maruthi T.
Abstract : Highlights: This work develops a plant monitoring system that is resilient to cyber attacks. A five-layer decentralized resilient monitoring system (RMS) is introduced. The RMS is applied to a simplified model of a power plant. The efficacy of the RMS is evaluated under several attack scenarios. The approach can be potentially used for design of RMS for critical infrastructures. Abstract: Resilient monitoring systems (RMS) are sensor networks that degrade gracefully under malicious attacks on their sensors, causing them to project misleading information. This paper develops techniques to ensure resiliency, namely: active data quality acquisition, process variable and plant condition assessments, sensor network adaptation, and plant decomposition with knowledge fusion. Based on these techniques, we design a RMS for power plants and investigate its performance under various cyber-physical attacks. In all scenarios considered, the system offers effective protection against misleading information and identifies the plant condition – normal or anomalous – in a reliable and timely manner.